Anti-Cancer Potential of Afzelin towards AGS Gastric Cancer Cells - Iwona Radziejewska; Katarzyna Supruniuk; Robert Czarnomysy; Kamila Buzun; Anna Bielawska (MDPI AG, 2021)
Afzelin demonstrates anti-inflammatory and anti-cancer properties. Our purpose was to assess its influence on apoptosis, Bax, caspases, MUC1, cancer-related carbohydrate antigens, enzymes participating in their formation, and galectin-3 in AGS gastric cancer cells. A total of 60 and 120 μM afzelin was used in all experiments. Flow cytometry was applied to determine apoptotic response. Western blotting and RT PCR were used to detect the expression of mentioned factors. Flavonoid at higher concentration revealed slight apoptotic respond. Bax, caspase-3, -8, -9 increased upon afzelin action. Stimulatory effect of the flavonoid on MUC1 cytoplasmic tail and extracellular domain in cell lysates and on MUC1 gene was revealed. MUC1 release into the culture medium was inhibited by the flavonoid. The 60 μM afzelin dose stimulated GalNAcTL5 protein expression and inhibited C1GalT1. ST6GalNAcT mRNA was inhibited by both flavonoid doses. ST3GalT was inhibited by 120 μM afzelin on protein and mRNA level. Lewisa/b protein was reduced by both afzelin concentrations. FUT3 and FUT4 mRNA was inhibited by 120 μM dose of afzelin. Galectin-3 protein increased in cell lysates and decreased in culture supernatant by 60 and 120 μM flavonoid. Galectin-3 gene expression was stimulated by two used concentrations of afzelin in comparison to control. We conclude that afzelin can be considered as the potential anti-cancer agent, supporting conventional cancer treatment.